2022
DOI: 10.1002/job.2595
|View full text |Cite
|
Sign up to set email alerts
|

The impact of work hours on work‐to‐family enrichment and conflict through energy processes: A meta‐analysis

Abstract: Summary We use a meta‐analysis to introduce a framework that integrates research on the relationship between working hours and the work–family interface. Using the work–home resources model, we integrate work–family enrichment and conflict theory, focusing on the positive and negative mediational processes of human energy. We conceptualize working hours, within the framework of the work–home resources model, as the potential to increase vigor and exhaustion in tandem, which, in turn, would lead to increased wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 327 publications
(307 reference statements)
0
17
0
Order By: Relevance
“…In another study (Greenhaus and Beatell, 1985), the family responsibilities of employees, considering that they would interfere with the work duties, which are generally called family-work conflict, examined the effect of family and work conflicts on job performance. Similar to studies showing that job performance changes daily, it is argued that family-work conflict can have a high impact (Pak, Kramer, Lee and Kim, 2022;Vallerand, 1997;Wang, Liu, Zhan, and Shi, 2010). In other word, intrinsic motivation can affect the job performance of the individual's family environment and may have a positive or negative effect on a general level (Nohe, Michael, and Sonntag 2014).…”
Section: Introductionmentioning
confidence: 82%
“…In another study (Greenhaus and Beatell, 1985), the family responsibilities of employees, considering that they would interfere with the work duties, which are generally called family-work conflict, examined the effect of family and work conflicts on job performance. Similar to studies showing that job performance changes daily, it is argued that family-work conflict can have a high impact (Pak, Kramer, Lee and Kim, 2022;Vallerand, 1997;Wang, Liu, Zhan, and Shi, 2010). In other word, intrinsic motivation can affect the job performance of the individual's family environment and may have a positive or negative effect on a general level (Nohe, Michael, and Sonntag 2014).…”
Section: Introductionmentioning
confidence: 82%
“…Thus, per the W‐HR model and other resource‐based theories, low energy levels should be a central, proximal cause of work–family conflict. Empirical research supports this in that exhaustion has been found to correlate strongly with work–family conflict (Pak et al, 2022), although this finding is based on cross‐sectional research.Hypothesis Energy resource levels negatively predict subsequent change in work–family conflict over a 1‐month period. …”
Section: Cross‐lagged Effects Among Personal Resources and Work–famil...mentioning
confidence: 97%
“…As a broad representation of the inner psychological state, personal resources include mood, physical and cognitive energy and so on (Ten Brummelhuis and Bakker, 2012). Following the previous work–family spillover literature as well as the core definition of personal resources in the work–home resources model, we adopt personal resources depletion as the overall capture of the quantity and quality of the personal resources in our research (Lin et al ., 2022; Pak et al ., 2022; Ten Brummelhuis et al ., 2022; Ten Brummelhuis and Bakker, 2012).…”
Section: Theoretical Overview and Hypotheses Developmentmentioning
confidence: 99%